Portuguese scientific output in medical education between 2013–2022: From local to global networks - Teresa Costa; Sofia Serra; Nuno Neuparth; António Rendas (Educación Médica)
Introduction: The scope of medical education (ME) as an autonomous field of study is still under debate. The present study aimed to identify publications addressing the topic of ME, published in international medical journals, by Portuguese authors, alone or in collaboration with foreign colleagues. Methods: Publications were retrieved from Scopus and Web of Science, between 2013 and 2022. Each publication was identified by title, name, and affiliation of the corresponding author. Affiliation of all authors was also taken into consideration to detect networks. Titles were used to identify subjects, complemented by keywords and abstract. Journal Citation Reports and Scimago Journal Rank indexed journals in the education category were identified and from these ME journals were selected.We chose 29 journals from which 17 had publications from Portuguese’s authors in a total of 80 publications. Results: The top journals in terms of productivity were BMC Medical Education, Medical Teacher, and Advances in Health Sciences Education. The Portuguese international cooperation involved Europe (United Kingdom, Spain, the Netherlands, and Ireland), North America (USA and Canada) and Oceania (Australia). Outside the Northen Hemisphere, cooperation involved mostly Brazil. Nationally, the dominant networks involved the Universities of Porto and Minho.Five core areas were identified namely “medical education”, “medical student”, “health care personnel”, “medical school”, and “undergraduate medical education”. Conclusion: Despite the limitations of this study because the search was only focused on ME journals it showed a trend towards internationalisation of some Portuguese authors, particularly those who were also involved in established national networks. Resumen: Introducción: El alcance de la educación médica como campo de estudio autónomo sigue siendo objeto de debate. El presente estudio tuvo como objetivo identificar las publicaciones que abordan el tema de la educación médica (EM), publicadas en revistas médicas internacionales, por autores portugueses, solos o en colaboración con colegas extranjeros. Métodos: Las publicaciones fueron recuperadas de Scopus y Web of Science, entre 2013 y 2022. Cada publicación fue identificada por título, nombre y afiliación del autor correspondiente. También se tuvo en cuenta la afiliación de todos los autores para detectar redes. Los títulos se utilizaron para identificar los temas, complementados por las palabras clave y el resumen. Se identificaron las revistas indexadas en Journal Citation Reports y Scimago Journal Rank en la categoría de educación y de ellas se seleccionaron las revistas de EM.Se seleccionaron 29 revistas de las cuales 17 tenían publicaciones de autores portugueses en un total de 80 publicaciones. Resultados: Las principales revistas en términos de productividad fueron BMC Medical Education, Medical Teacher y Advances in Health Sciences Education. La cooperación internacional portuguesa se centró en Europa (principalmente Reino Unido, España, Países Bajos e Irlanda), Norteamérica (EE.UU. y Canadá) y Oceanía (Australia). Fuera del hemisferio norte, la cooperación se centró principalmente en Brasil. A nivel nacional, las redes predominantes son las de las universidades de Oporto y Minho.